2016
DOI: 10.1017/s0954579416000766
|View full text |Cite
|
Sign up to set email alerts
|

Neural predictors of alcohol use and psychopathology symptoms in adolescents

Abstract: Adolescence is a period marked by increases in risk taking, sensation seeking, and emotion dysregulation. Neurobiological models of adolescent development propose that lagging development in brain regions associated with affect and behavior control compared to regions associated with reward and emotion processing may underlie these behavioral manifestations. Cross-sectional studies have identified several functional brain networks that may contribute to risk for substance use and psychopathology in adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…DHEA plays a central role in cortical plasticity in prefrontal (dorsolateral prefrontal cortex [dlPFC]; anterior cingulate [ACC]), parietal (temporal parietal junction [TPJ]), and subcortical structures (amygdala; hippocampus) involved in memory and attention (Nguyen et al., , ). Subsequently, relevant to the adolescent treatment context, DHEA has cognition‐promoting functions during adolescent development, particularly in emotionally “hot” situations (Brumback et al., ; Nguyen et al., ).…”
Section: The Nature Of the Adolescent Brain: Characteristic Features mentioning
confidence: 99%
“…DHEA plays a central role in cortical plasticity in prefrontal (dorsolateral prefrontal cortex [dlPFC]; anterior cingulate [ACC]), parietal (temporal parietal junction [TPJ]), and subcortical structures (amygdala; hippocampus) involved in memory and attention (Nguyen et al., , ). Subsequently, relevant to the adolescent treatment context, DHEA has cognition‐promoting functions during adolescent development, particularly in emotionally “hot” situations (Brumback et al., ; Nguyen et al., ).…”
Section: The Nature Of the Adolescent Brain: Characteristic Features mentioning
confidence: 99%
“…Previous studies have demonstrated that adolescents who are more likely to drink alcohol have thinner frontal cortices (Brumback et al, 2016; Silveri et al, 2016) and distributed regions in the frontal, parietal, temporal, and occipital lobes (in prediction models that including neuroimaging data (Silveri et al, 2016; Squeglia et al, 2016). A larger study of PHIV youth in the PHACS AMP study found that substance use among PHIV youth may lead to greater risky behavior (Alperen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, smaller volume or less gyrification in the orbitofrontal cortex at baseline predicts initiation of cannabis use over the course of 4 years (Cheetham et al, ), the emergence of substance use disorders over the course of 6 years (Cheetham et al, ), and increases in alcohol‐use related problems over the course of 2 years (Kuhn et al, ) during adolescence. However, other studies have not found significant associations between orbitofrontal morphometry at baseline and the initiation of alcohol use (Luciana, Collins, Muetzel, & Lim, ; Squeglia et al, ) or future episodes of binge drinking (Brumback et al, ). Taken together, these studies suggest that smaller volumes and thicknesses in frontolimbic regions predict future substance use.…”
Section: Substance Abusementioning
confidence: 93%
“…Studies of baseline gray‐matter morphology have found that volume, thickness, and gyrification in frontolimbic regions predict the later initiation and escalation of substance use. In adolescents, thinner anterior cingulate and ventrolateral prefrontal cortices at a baseline were associated with heavy alcohol use 3‐years later (Squeglia et al, ), and thinner dorsolateral prefrontal cortex predicted more binge drinking up to 13 years later (Brumback et al, ). Another study found that smaller anterior cingulate volume and higher levels of negative affect in 12 year olds increased the odds of experiencing alcohol‐related problems 4 years later (Cheetham et al, ).…”
Section: Substance Abusementioning
confidence: 99%